2020
DOI: 10.1080/13561820.2020.1712336
|View full text |Cite
|
Sign up to set email alerts
|

Supervisors’ pedagogies for supporting interns to learn intra- and interprofessional collaboration: a qualitative and quantitative ego network analysis

Abstract: This work aims to understand intra-and interprofessional networks of general practitioners (GPs) and ear, nose, and throat specialists (ENT specialists), and in what manner supervisors in these specialties involve interns in their professional network to help them learn intra-and interprofessional collaboration. An egocentric social network approach was used to collect and analyze quantitative as well as qualitative data. For this, semi-structured interviews were held with ten GP and ten ENT specialists. GPs h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Therefore, the educator should create conditions for this process to enhance learning in the individuals. As shown in the earlier study, interprofessional interaction generated a greater understanding of the participants’ roles and knowledge areas and improved the individual’s operational efficiency and, thereby, the group 5 13 14. Thus, joint reflections and discussions are considered unavoidable beneficial activity.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Therefore, the educator should create conditions for this process to enhance learning in the individuals. As shown in the earlier study, interprofessional interaction generated a greater understanding of the participants’ roles and knowledge areas and improved the individual’s operational efficiency and, thereby, the group 5 13 14. Thus, joint reflections and discussions are considered unavoidable beneficial activity.…”
Section: Introductionmentioning
confidence: 70%
“…Intraprofessional learning defines as learning between individuals of different disciplines within the same profession 12. Previous studies have shown that intraprofessional and interprofessional activities, such as collaboration, positively impact learning as the participants better understand their behaviour, professional roles and responsibilities, which are crucial for doing their job 13 14. In addition, it leads to better collaboration and communication between healthcare professionals, which is a more favourable basis to meet the need for care and support in the care receiver.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation